Smart Chinese medicine for hypertension treatment with a deep learning model. (1st March 2019) - Zhang, Qingchen; Bai, Changchuan; Chen, Zhikui; Li, Peng; Wang, Shuo; Gao, He
Abstract: As one important component of smart world, smart health is drawing more and more attention. Over the years, hypertension has become a high incident disease and it is continuing to threaten human health seriously. Unfortunately, no effective way has been found to cure hypertension at present. Many medical experiences have demonstrated the curative effect of traditional Chinese medicine in the hypertension treatment. In this paper, we explore smart Chinese medicine for hypertension treatment by combining deep learning and the traditional Chinese medicine theory. First, we present a potential idea to categorize the clinical cases into different groups based on symptom with the stacked auto-encoder model. Furthermore, we discuss and summarize the curative effect of classical prescriptions and herbs for each type of symptom in hypertension. Finally, we review the related work about deep learning models in medical application. The explored smart Chinese medicine is expected to guide doctors to treat hypertension diseases in clinical, which is helpful to build smart world, especially smart health.